Automated MIP-based in-tip dispersive micro-solid phase extraction for determination of ketoprofen in environmental water: A proof of concept and performance evaluation - Mohammed T. Shehabeldeen; Fotouh R. Mansour; Samah F. El-Malla; Aya A. Abdella (Talanta Open)
Automated in-tip dispersive micro-solid phase extraction is a miniaturized technique that could afford advantages of solid phase extraction with fewer steps and reduced environmental hazard. In this work, molecularly imprinted polymer was evaluated as a packing sorbent for a lab-made automated dispersive pipette tip extraction (MIP-DPX). The MIP was prepared using chitosan as the functional monomer, glutaraldehyde as the crosslinker, and ketoprofen (KTP) as the template molecule. The efficiency of KTP extraction using the devised automated tip was studied by investigating the effect of adsorption pH, elution volume, and the number of aspirating/dispensing cycles. High recovery rates were obtained at pH 4 employing 8 cycles of aspiration followed by KTP elution using methanol (500 μL) in a single dispensing cycle. The developed MIP-DPX demonstrated good linearity and reproducibility, making it suitable for KTP determination in environmental water. MIP-DPX was evaluated for environmental friendliness using the Complex Green Analytical Procedure Index (Complex GAPI) and Analytical GREEnness metric (AGREE), as well as practicality using the Blue Applicability Grade Index (BAGI). The developed workflow was proved to be a practical, environmentally friendly, and economic approach for pre-concentration and determination of KTP. The devised in-tip extraction system showed promising results paving the way for expanding the applicability of MIP-based SPE towards their automation.